Understanding the Impact of Food Delivery Services on University Students’ Purchase Intentions - Rosmelisa Yusof; Liem Gai Sin; Nursafiyyah Mohamed Fauzi; Nurul Afiqah Mohd Nasir; Nurul Alis Amira Ahmad Mahidin; Nurul Firzanah Mohd Suhaimi; Nurul Muzirah Syed Abu Bakar; A. J. Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
GrabFood, one of the leading food delivery applications, has become an essential part of university students’ daily consumption behavior due to its convenience and accessibility. This study aims to examine the factors influencing students’ purchase intentions toward GrabFood by focusing on convenience, price, design, and food variety as independent variables, with trustworthiness serving as a mediating factor. Using a quantitative research design, data were collected from 102 university students in Malaysia through a structured questionnaire and analyzed using multiple regression with SPSS. The results reveal that food variety (? = 0.422, p 0.05) and price (? = 0.343, p 0.05) are the strongest positive determinants of purchase intention, followed by convenience (? = 0.214, p 0.05). In contrast, design (? = ?0.041) and trustworthiness (? = 0.080) do not exhibit significant direct effects. The model explains 69.3% of the variance in purchase intention (R² = 0.693), underscoring the predominance of functional and value-based factors over aesthetic considerations. These findings suggest that GrabFood should continue prioritizing fair and transparent pricing, expanding menu diversity, and maintaining service reliability to strengthen user trust, satisfaction, and long-term loyalty among university students.